Withaferin A triggers G2/M arrest and intrinsic apoptosis in glioblastoma cells via ATF4‐ATF3‐CHOP axis. (23rd October 2019) - Tang, Qin; Ren, Liwen; Liu, Jinyi; Li, Wan; Zheng, Xiangjin; Wang, Jinhua; Du, Guanhua
Abstract: Objective: Withaferin A (WA) is a bioactive compound with a remarkable anti‐cancer effect derived from Withania somnifera, commonly known as ashwagandha. However, the anti‐cancer mechanisms of WA in glioblastoma multiforme (GBM) are still unclear. Materials and Methods: Cell viability assays and xenografted nude mice were used to evaluate the effects of WA, along with flow cytometry to detect apoptosis and cell cycle of GBM. RNA‐seq analysis, Western blotting, immunofluorescence staining, qRT‐PCR and siRNA gene silencing were carried out to determine the signalling pathways affected by WA. Results: Withaferin A significantly inhibited the growth of GBM in vitro and in vivo and triggered the intrinsic apoptosis of GBM cells by up‐regulating expression of Bim and Bad. WA arrested GBM cells at the G2/M phase of the cell cycle through dephosphorylating Thr 161 of CDK1 by activating p53‐independent p21 up‐regulation. Knockdown of p21 restored cell cycle progression and cell viability by down‐regulating the expression of Bad rather than Bim. We demonstrated that endoplasmic reticulum (ER) stress induced by WA through the ATF4‐ATF3‐CHOP axis, initiated apoptosis and G2/M arrest in GBM cells. Conclusion: We revealed a novel pathway that elucidated WA activation of apoptosis and G2/M arrest in GBM cells through the ATF4‐ATF3‐CHOP axis. This discovery is important for optimization of WA‐based regimens for prevention and/or treatment of GBM.